2019
DOI: 10.1017/s1355770x19000020
|View full text |Cite
|
Sign up to set email alerts
|

Financing environmentally-sustainable projects with green bonds

Abstract: A structural model for green bonds is developed to explain the formation and dynamics of green bond prices and to address the issue of the so-called ‘greenium’, that is, the difference between the yields on a conventional bond and a green bond with the same characteristics. We provide answers to the following questions: What are the determinants of the green bond value? Do green bonds enhance the credit quality of the issuer? Are green bonds a relatively cheap tool to fund sustainable investments? We also stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(94 citation statements)
references
References 12 publications
3
85
0
6
Order By: Relevance
“…This number appears small compared to the size of total European domiciled bond fund assets with about EUR 2.5 trillion as of December 2018 (Sewell 2019). The rising environmental awareness among investors contributes to an increased demand for green bonds and to oversubscriptions, thus enabling the funding of eco-friendly projects in a cheaper way (Agliardi and Agliardi 2019).…”
Section: For Issuers a Formidable Marketing Toolmentioning
confidence: 99%
“…This number appears small compared to the size of total European domiciled bond fund assets with about EUR 2.5 trillion as of December 2018 (Sewell 2019). The rising environmental awareness among investors contributes to an increased demand for green bonds and to oversubscriptions, thus enabling the funding of eco-friendly projects in a cheaper way (Agliardi and Agliardi 2019).…”
Section: For Issuers a Formidable Marketing Toolmentioning
confidence: 99%
“…The notion of "greenium" has also been treated by Agliardi and Agliardi (2019), who questioned the financial interest of a Green Bond as a funding tool. The authors conclude that this green premium, that would make Green bonds a cheaper than conventional bonds, might be even more present and important for Green bond issuances with a high underlying asset volatility, high parameters that govern the green underlying technology, and low corporate tax rates.…”
Section: Green Bond Marketmentioning
confidence: 99%
“…Onwezen & Bartels also found that practitioners who have a positive emotion of belonging to tourism are more inclined to engage in friendly behaviour towards tourists [12]. Agliardi E & Agliardi R point out some respondents linked protective behaviour to time costs and higher spending constraints, although most of them showed better awareness their hazards of the pandemic and more positive attitudes of preventing COVID-19 [13]. Olya and Akhshik also consider that the barriers of proactive protection behaviour, including money cost, emotional input and awareness of responsibility [14].…”
Section: Personal Protective Intention Of Local Tourism Practitionermentioning
confidence: 99%